Disparities in survival by insurance status in patients with Hodgkin lymphoma. Issue 19 (8th June 2015) - Parikh, Rahul R.; Grossbard, Michael L.; Green, B. Lee; Harrison, Louis B.; Yahalom, Joachim
<x xml:space="preserve">Abstract</x> BACKGROUND The association between insurance status and outcomes has not been well established for patients with Hodgkin lymphoma (HL). The purpose of this study was to examine the disparities in overall survival (OS) by insurance status in a large cohort of patients with HL. METHODS The National Cancer Data Base (NCDB) was used to evaluate patients with stage I to IV HL from 1998 to 2011. The association between insurance status, covariables, and outcomes was assessed in a multivariate Cox proportional hazards model. Survival was estimated with the Kaplan‐Meier method. RESULTS Among the 76, 681 patients within the NCDB, 45, 777 patients with stage I to IV HL were eligible for this study (median follow‐up, 6.0 years). The median age was 39 years (range, 18‐90 years). The insurance status was as follows: 3247 (7.1%) were uninsured, 7962 (17.4%) had Medicaid, 30, 334 (66.3%) had private insurance, 3746 (8.2%) had managed care, and 488 (1.1%) had Medicare. Patients with an unfavorable insurance status (Medicaid/uninsured) were at a more advanced stage, had higher comorbidity scores, had B symptoms, and were in a lower income/education quartile (all P < .01). These patients were less likely to receive radiotherapy and start chemotherapy promptly and were less commonly treated at academic/research centers (all P < .01). Patients with unfavorable insurance had a 5‐year OS of 54% versus 87% for those favorably insured (P < .01). When adjustments were made for covariates, an unfavorable insurance status was associated with significantly decreased OS (hazard ratio, 1.60; 95% confidence interval, 1.34‐1.91; P < .01). The unfavorable insurance status rate increased from 22.8% to 28.8% between 1998 and 2011. CONCLUSIONS This study reveals that HL patients with Medicaid and uninsured patients have outcomes inferior to those of patients with more favorable insurance. Targeting this subset of patients with limited access to care may help to improve outcomes. Cancer 2015;121:3435–43. © 2015 American Cancer Society.